FRI0144 Adalimumab trough level in blood corresponding with clinical response. (23rd January 2014) - Pouw, M.F.; Krieckaert, C.L.; Nurmohamed, M.T.; Rispens, T.; Aarden, L.; Wolbink, G.
Abstract : Background: Adalimumab is a recombinant human IgG1 monoclonal antibody with high specific binding to human tumor necrosis factor a (TNF). Since 2002 the drug has been approved for the treatment of rheumatoid arthritis (RA) and while several tests have been developed for testing drug levels and immunogenicity, the correlation between serum trough concentrations of this drug and therapeutic effect in clinical practice has not been studied yet. We propose that monitoring drug levels could make this treatment more cost-effective, specially considering the high costs of biologicals. Objectives: To investigate the correlation between clinical improvement and serum trough concentrations of adalimumab in RA patients, 6 months after start of treatment. Methods: Prospective cohort consisting of 201 patients treated with 40mg adalimumab every two weeks. Six months after start of treatment serum trough adalimumab levels were measured by ELISA. Clinical improvement was defined as the difference in Disease Activity Score 28 (DAS28) of the patients before start of the treatment, and after six months. Randomizing data as groups of ten patients gives a median trough and median Delta DAS28 (DDAS28). These findings were studied in a concentration-effect curve. Results: After 6 months of treatment, serum trough concentrations varied between 0 to 33 ug/mL. Patients without detectable adalimumab did not respond clinically. All of these patients had developed anti-adalimumab antibodies. In patients with serum levels ranging from 3 to 12 ug/mL clinical response seemed to be related to serum adalimumab levels. Higher levels of adalimumab did not contribute further to clinical improvement. Conclusions: This study indicates that serum trough levels of adalimumab fluctuate widely. To achieve clinical effect in RA, serum levels of 3 to 12 ug/mL could be sufficient. Hence, this suggests that presently a significant amount of patients is overtreated. Obviously, monitoring of drug levels is needed leading to personalized medication schemes allowing a more rational usage of this drug. Disclosure of Interest: None Declared